ダイ16ジ エットウ タイイン ノ タイナイ ホウシャセイ ブッシツ ^<137>Cs ^<40>K ノ ソクテイ ホウコク I - 宮下, 充正; ミヤシタ, ミツマサ; 跡見, 順子; アトミ, ヨリコ; 上田, 慶子; ウエダ, ケイコ; MIYASHITA, Mitsumasa; ATOMI, Yoriko; UEDA, Keiko (国立極地研究所, 1975)
P(論文) The radioactive nuclides in human body are roughly classified into two categories. The one is naturally existed radioactive nuclides, and the other is radioactive nuclides of fallout from the nuclear fission of a large scale such as tests of nuclear weapon. In the present study, body burdens of Cesium-137 and Potassium-40 were measured using a human counter with twenty-one members of the 16th wintering party. The purposes of those measurements were (1) to observe the radioactive pollution in Japan and Antarctica through the human body, and (2) to estimate the effect of the Antarctic living on the work capacity through the change in body composition, since natural potassium which exists mostly in the active tissues of the human body contains ^<40>K in a constant ratio (0.012%). There was no individual difference in ^<137>Cs content among the members who live in various parts of Japan. Its mean value was 1.40±0.43 (nCi) and the lowest among the values obtained for Japanese during the last decade. The aerobic work capacity of the members which was estimated from the total body potassium was almost the same with the ordinary healthy men. After the members have returned to Japan the second measurements will be needed for further discussion and conclusion. departmental bulletin paper